2016
DOI: 10.3329/bjp.v11i3.26181
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic potential of <i>Silybum marianum</i> seeds in pentylenetetrazol-induced kindled mice

Abstract: <p class="Abstract">Epilepsy is an abnormality of nervous system showing seizures. Despite, the known antiepileptic activity of plants possessing anti-oxidant properties, <em>Silybum marianum</em> has not been studied yet. Therefore, present experiment was planned to evaluate antiepileptic potential of <em>S. marianum</em> (100, 200 and 300 mg/kg) seeds ethanol extract in pentylenetetrazol-induced kindled mice (n = 30). <em>S. marianum</em> seed extract (300 mg/kg) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Hence, it will be essential to pay attention to traditional medicine and herbal medicines to achieve low-risk drugs with minimal side effects (Rostampour et al, 2014). The plants such as Aitchisonia rosea (Rasool et al, 2015), Bacopa monnieri (Paulose et al, 2008), Cannabis sativa (Leite and Carlini, 1973), Cyperus articulates (Bakanova and Leutskií, 2971), Sechium edule (Mumtaz et al, 2012), Silybum marianum (Waqar et al, 2016) and Zizyphus jujube (Puhaja et al, 2011) showed antiepileptic effect. (Wan et al, 2017), and sedative (Amos et al, 2003) effects in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it will be essential to pay attention to traditional medicine and herbal medicines to achieve low-risk drugs with minimal side effects (Rostampour et al, 2014). The plants such as Aitchisonia rosea (Rasool et al, 2015), Bacopa monnieri (Paulose et al, 2008), Cannabis sativa (Leite and Carlini, 1973), Cyperus articulates (Bakanova and Leutskií, 2971), Sechium edule (Mumtaz et al, 2012), Silybum marianum (Waqar et al, 2016) and Zizyphus jujube (Puhaja et al, 2011) showed antiepileptic effect. (Wan et al, 2017), and sedative (Amos et al, 2003) effects in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 300 mg/kg Silybum marianum seed extract was used, which demonstrate the obvious stability against PTZ-induced convulsions (fatality, duration, and seizure frequency). Moreover, a 300 mg/kg dose of the extract was observed to be efficient in preventing oxidative stress in the brain of mice, leading to significantly higher antiepileptic activity …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a 300 mg/kg dose of the extract was observed to be efficient in preventing oxidative stress in the brain of mice, leading to significantly higher antiepileptic activity. 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silybum marianum is another anticonvulsive herbal with antioxidant and antiseizure effects, lowering the frequency and duration of convulsions in PTZ experimental mice and reducing PTZ-induced lethality [ 64 ] (Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%